Characterization of CoNI-Sn catalyst for autothermal reforming methane - Songip, Ahmad Rahman; Nasri, N. S.; Tutuk, D. K.; Ismail, S. R. (Universiti Teknologi Petronas, 2004)
Autothermal reforming (ATR) is a combination of steam reforming and partial oxidation process. It is a one of the methods in producing hydrogen from natural gas. CoNiSn with different catalyst supports e.g. MgO and Al2O3 has been chose to be used on this autothermal reforming of methane (ATR). The objective of this paper is to study the bulk structure of the catalyst using Temperature Programed Reduction (TPR) and X-ray Diffraction (XRD). From the TPR and XRD, the addition of tin into MgO-supported catalyst will become the anti coking agent, as it will react with carbide, since it is deposited at the outer layer of the matrix CoO-NiO-MgO solid solution phase.